Impact of parity and pre-pregnancy BMI on second-trimester sFlt-1 and PlGF levels in normotensive pregnancies - Motoaki Kinugawa; Keiichi Kumasawa; Kazunari Nemoto; Keisuke Nakajima; Mari Ichinose; Masatake Toshimitsu; Seisuke Sayama; Takahiro Seyama; Takayuki Iriyama; Yasushi Hirota; Yutaka Osuga (Hypertension in Pregnancy)
Background Advanced maternal age, obesity, and primiparity are established risk factors for preeclampsia (PE). While soluble fms-like tyrosine kinase 1 (sFlt-1) and placental growth factor (PlGF) are key biomarkers for predicting PE, their variation based on maternal background factors remains unclear. This study aimed to identify maternal factors associated with sFlt-1 and PlGF levels.Methods We analyzed blood concentrations of sFlt-1 and PlGF in 830 pregnant women during the second trimester. Multivariate analysis was performed to examine their associations with maternal background factors. Based on the results, pregnant women who did not develop PE or superimposed PE were categorized by parity (0, 1, and ≥2) and pre-pregnancy BMI (<18.5, 18.5–25, and ≥25), and comparisons were conducted within each category.Results Multivariate analysis revealed that sFlt-1 was affected by parity and pre-pregnancy BMI, while PlGF was influenced by pre-pregnancy BMI. Multiparous women exhibited lower sFlt-1 and sFlt-1/PlGF ratios than primiparous women. Additionally, women with a BMI ≥ 25 showed lower sFlt-1 and PlGF levels, but higher sFlt-1/PlGF ratios than those with a BMI < 25.Conclusion These findings suggest differences in placental development based on maternal background factors and raise the possibility that parity and BMI could influence the interpretation of cutoff values for PE prediction.